Sub-regional activation of supraspinatus and infraspinatus muscles during activities of daily living is task dependent. (October 2020) - Lulic-Kuryllo, Tea; Alenabi, Talia; McDonald, Alison C.; Kim, Soo Y.; Dickerson, Clark R.
Abstract: The supraspinatus and infraspinatus muscles each have multiple sub-regions that may activate differentially in activities of daily living. Awareness of these differential demands critically informs rehabilitation of rotator cuff muscle following injury, particularly if centered on recovering and strengthening the rotator cuff to perform daily tasks. This study quantified muscle activation of supraspinatus and infraspinatus sub-regions during the performance of six activities of daily living. Twenty-three participants (mean: 22.6 ± 2.6 years) completed the following tasks: opening a jar, reaching at shoulder height, overhead reaching, pouring water from a pitcher, eating with a spoon, and combing hair. Indwelling electromyography was collected from the anterior and posterior supraspinatus and superior, middle, and inferior infraspinatus. Tasks requiring high arm elevations (e.g. reaching at shoulder and overhead height) activated anterior supraspinatus between 21 and 28% MVC. The posterior supraspinatus consistently activated between 10 and 30% MVC across all tasks. All sub-regions of infraspinatus activated highly (between 18 and 25% MVC) in tasks requiring high arm elevations in flexion. These findings may be leveraged to define effective measures to increase rotator cuff function in daily tasks.